Governance and Performance Management in Public Universities Current Research and Practice - Caperchione, Eugenio; Bianchi, Carmine (Cham : Springer International Publishing : Imprint: Springer, 2022)
This edited volume contributes to the ongoing research and practice on applying performance management to university governance. A comparative approach and international perspective of the issue is provided through extensive use of case studies and empirical findings. A specific focus is also placed on using performance governance applied to higher education institutions' Third Mission, and on enhancing decision makers' ability to frame dynamic complexity. In this regard, specific attention is devoted to analyzing the cause-and-effect relationships in affecting public outcomes. This also includes managing trade-offs in both time and space, and detecting and counteracting unintended behavioral effects from the use of formal systems focused on quantitative measures for performance assessment.
Performance Management and Governance in Public Universities: Challenges and Opportunities -- Transparency and Accountability in Higher Education as a Response to External Stakeholders and Rules: A Comparison Between Three Country-Case Studies -- An Analysis of Methodologies, Incentives, and Effects of Performance Evaluation in Higher Education: The English Experience -- A Longitudinal Analysis of the Relationship Between Central Government and Universities in France: The Role of Performance Measurement Mechanisms -- Adopting a Dynamic Performance Governance Approach to Frame Interorganizational Value Generation Processes into a University Third Mission Setting -- The Third Mission Strategies Disclosure Through the Integrated Plan -- Transferring Knowledge to Improve University Competitiveness: The Performance of Technology Transfer Offices -- Third Mission and Intellectual Capital External Dimension: The Implications in the European University Planning Process -- Institutional Logics to Unveil Entrepreneurial Universities' Performances: A Cross-Country Comparative Study -- Third Mission in Universities from a Performance Management Perspective: A Comparison Between Germany and Italy.
Keywords: Industrial organization; Education, Higher; Education-Economic aspects; Education and state; Organization; Higher Education; Education Economics; Educational Policy and Politics